(untitled) (Enki & Ptah. Journal of Technology and Trade in Ancient Egypt and Western Asia, 2025)
The aim of this paper is to provide a comprehensive overview on the A-Horizon, the most ancient Lower Nubian culture, and on its relationship with the emerging Egyptian State, overcoming the long-standing colonial perspective and adopting the post-colonial approach currently applied in the MENA region. To better understand the different developmental trajectories between Egypt and Lower Nubia, it is necessary to review the geographical framework of the region, also considering paleoenvironmental research, focusing on the prehistoric premises of Nubian cultural facies. Then, a concise overview on the challenges scholars face in determining an absolute chronology for the transitional age between prehistory and protohistory is crucial to set the incipient statalisation in the Nile Valley against a solid background. Furthermore, the analysis of the A-Horizon culture must be conducted by highlighting the episodes of contact and divergence with the Egyptian world, addressing both instances of mutual hostility and elements of creolisation which made Lower Nubia a key interface between different cultural horizons. The paper focuses on three A-Horizon cemeteries, which share strong hybrid Egyptian-Nubian features: Cemetery 7 at Shellal, dating to Early A-Horizon, the Classical-terminal A-Horizon Cemetery 137 at Sayala and Cemetery L at Qustul, chronologically set within the full Terminal A-Horizon. The purpose is twofold: displaying the transformations in funerary customs (and, consequently, in Nubian society) through time, and highlighting regional differences between lower and upper Lower Nubia. This aims to encourage renewed research in an area currently submerged by Lake Nasser, hence no longer investigable through direct archaeological fieldwork.